Blood glucose control for patients with acute coronary syndromes in Qatar - Kyle John Wilby; Eman Elmekaty; Ibtihal Abdallah; Masa Habra; Khalid Al-Siyabi (Elsevier, 2016)
Background: Blood glucose is known to be elevated in patients presenting with acute coronary syndromes. However a gap in knowledge exists regarding effective management strategies once admitted to acute care units. It is also unknown what factors (if any) predict elevated glucose values during initial presentation. Objectives: Objectives of the study were to characterize blood glucose control in patients admitted to the cardiac care unit (CCU) in Qatar and to determine predictive factors associated with high glucose levels (>10 mmol/l) on admission to the CCU. Setting: All data for this study were obtained from the CCU at Heart Hospital in Doha, Qatar. Method: A retrospective chart review was completed for patients admitted to the CCU in Qatar from October 1st, 2012 to March 31st, 2013, of which 283 were included. Baseline characteristics (age, gender, nationality, medical history, smoking status, type of acute coronary syndrome), capillary and lab blood glucose measurements, and use of insulin were extracted. Time spent in glucose ranges of <4, 4 to <8, 8 to <10, and >10 mmol/1 was calculated manually. Univariate and multivariate logistic regression were performed to assess factors associated with high glucose on admission. The primary analysis was completed with capillary data and a sensitivity analysis was completed using laboratory data. Main outcome measure: Blood glucose values measured on admission and throughout length of stay in the CCU. Results: Capillary blood glucose data showed majority of time was spent in the range of >10 mmol/l (41.95%), followed by 4-8 mmol/l (35.44%), then 8-10 mmol/l (21.45%), and finally <4 mmol/l (1.16%). As a sensitivity analysis, laboratory data showed very similar findings. Diabetes, hypertension, and non-smoker status predicted glucose values >10 mmol/l on admission (p < 0.05) in a univariate analysis but only diabetes remained significant in a multivariate model (OR 23.3; 95% CI, 11.5-47.3). Conclusion: Diabetes predicts high glucose values on hospital admission for patients with ACS and patients are not being adequately controlled throughout CCU stay. Keywords: Diabetes, Acute coronary syndromes, Glucose, Critical care, Myocardial Infarction